Responding to wheat blast: Multi-stakeholder "Precision Phenotyping Platforms (PPP)" and the development then release of blast resistant varieties. - CGIAR Research Program on Wheat (2021)
Wheat blast is an emerging fungal disease that has spread across continents (Brazil, Paraguay, Argentina, Bolivia, Bangladesh and Zambia). Researchers identified sources of resistance, deciphered the underlying resistance mechanism and developed resistant varieties, released in Bangladesh, Bolivia, India and Nepal. Seed multiplication and dissemination are in progress in these countries. The wheat blast pathogen’s population is clonal in Bangladesh with sensitivity to fungicides. Recent unpublished results indicate a close relationship of the Zambian with the Brazilian MoT population.